Impact of induction chemotherapy with concurrent chemoradiotherapy on nasopharyngeal carcinoma: A meta-analysis of randomized controlled trials - Huang, Ting-Chieh; Chen, Chi-Jen; Ding, Yi-Fang; Kang, Yi-No (Frontiers in Oncology, 2022)
Purpose Induction chemotherapy followed by concurrent chemoradiotherapy (IC-CCRT) may be beneficial for nasopharyngeal carcinoma. However, the evidence on medium- and long-term effects of IC-CCRT is limited, and new randomized controlled trials (RCTs) have been published after 2018. Therefore, this systematic review and meta-analysis compared survival rates between patients with nasopharyngeal carcinoma receiving IC-CCRT or concurrent chemoradiotherapy (CCRT). Methods Four databases were searched for RCTs on this topic. Two authors independently selected studies, assessed evidence, and extracted data on progression-free survival, overall survival, metastasis-free survival, and local recurrence-free survival. Available data were pooled in a random-effects model and mainly presented in hazard ratio (HR). Heterogeneity and small study effects were also evaluated. Results Eleven RCTs (n = 3345) were deemed eligible. Pooled results revealed that patients receiving IC-CCRT had significantly improved progression-free survival (HR = 0.66, P < 0.05), overall survival (HR = 0.64, P < 0.05), metastasis-free survival (HR = 0.58, P < 0.05), and local recurrence-free survival (HR = 0.69, P < 0.05) at 3 years, but no significant difference in 5-year overall survival was noted between IC-CCRT and CCRT (HR = 0.84, P > 0.05). Most findings had low heterogeneity. Conclusion IC-CCRT may benefit patients with nasopharyngeal carcinoma in the medium term, although no significant difference was observed in 5-year survival compared with CCRT. All outcomes had decreased survival rate from the 3-years to 5-year follow-up. Differences in patient ethnicities and regimens of IC-CCRT may be sources of heterogeneity.